Study of physic and organoleptic of butter developed using milk from cow and goat reared in Sleman Regency, Yogyakarta, Indonesia - Murti, T. W.; Pradana, M. W. E.; Nurasri, A. D.; Arlinda, M. (Journal of the Indonesian Tropical Animal Agriculture, 2020)
This study was to see physic-organoleptic of butter from goat as compared to cow butter reared in the Mt Merapi, Sleman regency, Yogyakarta. Both butter has been evaluated their fat size and numbers, the value of hardness, melting point, spreading and organoleptic performance. Fat size and numbers have evaluated microscopically, hardness by penetrometer, butter melting point at different temperature 30, 40, and 50 oC, as well as spreading by pressing down with ± 300 gram of weights. Organoleptic performances have been evaluated by panelist. The result of both butter were good. Goat butter contained more number of small-size fat globule lead to softer butter with hardness 0.3 kg/cm2 than cow butter with hardness more than 1.0 kg/cm2. Goat butter have melted faster than cow butter. Cow butter spreading were less rapid with 6 minutes than 1.5 minutes of goat butter. Panelist acceptance of cow butter were bigger than goat butter. It has been concluded that cow butter have had physically hard performance and well accepted than goat butter. Goat butter have presented well as fresh butter than storage butter.